Changing the threshold-Signals and mechanisms of mast cell priming - Halova, Ivana; Rönnberg, Elin; Draberova, Lubica; Vliagoftis, Harissios; Nilsson, Gunnar P; Draber, Petr (Immunological reviews, 2018)
Mast cells play a key role in allergy and other inflammatory diseases involving engagement of multivalent antigen with IgE bound to high-affinity IgE receptors (FcεRIs). Aggregation of FcεRIs on mast cells initiates a cascade of signaling events that eventually lead to degranulation, secretion of leukotrienes and prostaglandins, and cytokine and chemokine production contributing to the inflammatory response. Exposure to pro-inflammatory cytokines, chemokines, bacterial and viral products, as well as some other biological products and drugs, induces mast cell transition from the basal state into a primed one, which leads to enhanced response to IgE-antigen complexes. Mast cell priming changes the threshold for antigen-mediated activation by various mechanisms, depending on the priming agent used, which alone usually do not induce mast cell degranulation. In this review, we describe the priming processes induced in mast cells by various cytokines (stem cell factor, interleukins-4, -6 and -33), chemokines, other agents acting through G protein-coupled receptors (adenosine, prostaglandin E2 , sphingosine-1-phosphate, and β-2-adrenergic receptor agonists), toll-like receptors, and various drugs affecting the cytoskeleton. We will review the current knowledge about the molecular mechanisms behind priming of mast cells leading to degranulation and cytokine production and discuss the biological effects of mast cell priming induced by several cytokines.
Keywords: Chemokines; chemokiny; imunizace; signální transdukce; Receptors, G-Protein-Coupled; Signal Transduction; imunoglobulin E; Toll-Like Receptors; Cell Degranulation; alergie; cytokiny; cytokine receptors; high-affinity IgE receptor; chemokines; Hypersensitivity; toll-like receptory; receptory IgE; Mast Cells; Immunoglobulin E; cytokines; Receptors, IgE; Cytokines; mastocyty; Inflammation Mediators; receptory spřažené s G-proteiny; mast cell; cell priming; mediátory zánětu; degranulace buněk; Immunization